Secrets and Likes: The Drive for Privacy and the Difficulty of Achieving It in the Digital Age - Acquisti, Alessandro; Brandimarte, Laura; Loewenstein, George (Journal of Consumer Psychology, 2020)
We review different streams of social science literature on privacy with the goal of understanding consumer privacy decision making and deriving implications for policy. We focus on psychological and economic factors influencing both consumers' desire and consumers' ability to protect their privacy, either through individual action or through the implementation of regulations applying to firms. Contrary to depictions of online sharing behaviors as careless, we show how consumers fundamentally care about online privacy, and present evidence of numerous actions they take to protect it. However, we also document how prohibitively difficult it is to attain desired, or even desirable, levels of privacy through individual action alone. The remaining instrument for privacy protection is policy intervention. However, again for both psychological and economic reasons, the collective impetus for adequate intervention is often countervailed by powerful interests that oppose it.